Impulsive Antiperiodic Boundary Value Problems for Nonlinear qk-Difference Equations - Lihong Zhang; Bashir Ahmad; Guotao Wang (Abstract and Applied Analysis)
We show the existence and uniqueness of solutions for an antiperiodic boundary value problem of nonlinear impulsive qk-difference equations by applying some well-known fixed point theorems. An example is presented to illustrate the main results.